Cheated : The UNC Scandal, the Education of Athletes, and the Future of Big-Time College Sports - Smith, Jay M.; Willingham, Mary (Book collections on Project MUSE., 2015)
"Written by UNC professor of history Jay Smith and UNC athletics department whistleblower Mary Willingham, Cheated exposes the fraudulent inner workings of this famous university. For decades these internal systems have allowed woefully underprepared basketball and football players to take fake courses and earn devalued degrees from one of the nation's top universities while faculty and administrators looked the other way. In unbiased and carefully sourced detail, Cheated recounts the academic fraud in UNC's athletics department, even as university leaders focused on minimizing the damage in order to keep the billion-dollar college sports revenue machine functioning. Smith and Willingham make an impassioned argument that the "student-athletes" in these programs are being cheated out of what, after all, is promised them in the first place: a college education."--